2019
DOI: 10.3389/fneur.2019.00892
|View full text |Cite
|
Sign up to set email alerts
|

Communication About OFF Periods in Parkinson's Disease: A Survey of Physicians, Patients, and Carepartners

Abstract: Background: OFF periods impair quality of life in Parkinson's disease and are often amenable to treatment. Optimal treatment decisions rely on effective communication between physicians, patients and carepartners regarding this highly variable and complex phenomenon. Little is published in the literature about communication about OFF periods. Methods: Informed by interviews with physicians, patients and carepartners we designed questionnaires for each group. We surveyed these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Although the use of questionnaires to identify and communicate about off symptoms is seen as useful by PD patients, their care partners, and healthcare providers, our results highlight the limitations of using lists as tools in isolation to capture the patient experience in clinical practice. The results are also in keeping with the previous finding that patients with PD value the narrative interview as the most important facilitator of communication with their neurologist related to wearing off, and neurologists rate talking with their patients as the most important facilitator of discussions related to off periods . Our findings highlight the value of gathering unstructured, open‐ended data from individuals with PD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the use of questionnaires to identify and communicate about off symptoms is seen as useful by PD patients, their care partners, and healthcare providers, our results highlight the limitations of using lists as tools in isolation to capture the patient experience in clinical practice. The results are also in keeping with the previous finding that patients with PD value the narrative interview as the most important facilitator of communication with their neurologist related to wearing off, and neurologists rate talking with their patients as the most important facilitator of discussions related to off periods . Our findings highlight the value of gathering unstructured, open‐ended data from individuals with PD.…”
Section: Discussionsupporting
confidence: 90%
“…The results are also in keeping with the previous finding that patients with PD value the narrative interview as the most important facilitator of communication with their neurologist related to wearing off, and neurologists rate talking with their patients as the most important facilitator of discussions related to off periods. 17 Our findings highlight the value of gathering unstructured, open-ended data from individuals with PD. Such information is useful in determining what bothers patients and what they value most.…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that patients do not report their symptoms because of their own lack of knowledge or misunderstanding. Indeed, a recent study identified barriers in communications about OFF periods between healthcare providers and PD patients who often perceived that their OFF periods were part of the disease, so could not be improved by physician’s intervention [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agreement was more likely for motor symptoms; when a figurative language phrase was interpreted as representing a nonmotor symptom, agreement for which specific symptom was represented was low. This lack of agreement on over half of phrases may reflect a combination of factors, including the heterogeneity intrinsic to PD, 23 the broad range of ways in which patients experience complex PD manifestations and communicate about them, 24 , 25 and the inherently subjective nature of interpreting figurative language. 26 These and other factors may lead to misunderstandings in communication about off periods and, in turn, their suboptimal detection 12 and treatment.…”
Section: Discussionmentioning
confidence: 99%